Three trends in higher education and their potential impact on information agencies. Issue 1 (9th February 2015) - Cervone, H Frank
Abstract : Purpose: – In this paper three technological trends are explored. While these trends are not directly related to each other, the author posits that they are all manifestations of areas where libraries and librarians could play a more active role in using the technology to further the mission of the library. Taken together, the author discusses how these trends become a call to action for libraries and librarians to more directly engage in areas of responsibility outside their traditional domain if they wish to maintain a relevant role in the academy. Design/methodology/approach: – In this paper, an analysis of three of the trends discussed in the "NMC Horizon Project short list: 2013 higher education edition" report is undertaken. From this analysis, the author evaluates the relevance, in both the short- and long-terms, of these trends to academic libraries. Findings: – These three trends represent areas where libraries and librarians should attempt to become more directly involved in either using or exploiting technology. While two of these trends involve technology that is outside the traditional boundaries of librarianship, each of these technology trends will be increasingly critical to the higher education environment and it would behoove librarians to be at the forefront of thought leadership in these areas. Originality/value: – In this article, the author takes what seem to be unrelated trends and finds a common thread among them. Part of understanding how the needs of a library's user community may evolve over time is through identifying how a number of factors, many apparently unrelated, come together to change the overall focus and direction of patron needs. By looking at technology trends that are seemingly unrelated to libraries directly, the author develops a picture of what future directions academic libraries may take if they desire to maintain relevancy in a rapidly evolving technological landscape.